The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/md.0000000000018886
|View full text |Cite
|
Sign up to set email alerts
|

Multi-stage surgery combined with radiotherapy for treatment of giant anterior chest wall keloid

Abstract: Rationale: Giant keloids often have indications for surgical resection, but postoperative reconstruction of the skin and high recurrence of keloids are a challenge for clinical treatment. This article reports a rare successful treatment of a giant keloid in the anterior chest wall by multistage surgery combined with radiotherapy, which is why this case is meaningful. Patient concerns: A 66-year-old woman presented a giant keloid with ulcerations and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Keloids are common in African, Spanish, and Asian populations, with an incidence ranging from 4.5 to 16%, and cause itching, pain, and a burning sensation (Niessen et al, 1999). Keloids can occur within years, and more likely after an inciting stimulus such as dermal injury or an inflammatory process (Limandjaja et al, 2020); however, they are most often found on the chest, shoulders, upper back, and back of the neck, where skin tension is higher than in other areas of the body (Ogawa et al, 2012;Liu et al, 2020). In addition, keloids tend to occur on the earlobes as a result of ear piercing, burns, or surgical procedures.…”
Section: Fibrosis Keloids and Hypertrophic Scarsmentioning
confidence: 99%
“…Keloids are common in African, Spanish, and Asian populations, with an incidence ranging from 4.5 to 16%, and cause itching, pain, and a burning sensation (Niessen et al, 1999). Keloids can occur within years, and more likely after an inciting stimulus such as dermal injury or an inflammatory process (Limandjaja et al, 2020); however, they are most often found on the chest, shoulders, upper back, and back of the neck, where skin tension is higher than in other areas of the body (Ogawa et al, 2012;Liu et al, 2020). In addition, keloids tend to occur on the earlobes as a result of ear piercing, burns, or surgical procedures.…”
Section: Fibrosis Keloids and Hypertrophic Scarsmentioning
confidence: 99%
“…These neurotransmitters consist of histamine, acetylcholine, bradykinin, and proteinase. The itching sensation in the wound healing process is caused by an inflammatory response and partly due to the presence of mast cells in the wound area [28][29][30].…”
Section: Discussionmentioning
confidence: 99%